2017
DOI: 10.1038/s41598-017-16283-8
|View full text |Cite|
|
Sign up to set email alerts
|

Highly (001)-textured p-type WSe2 Thin Films as Efficient Large-Area Photocathodes for Solar Hydrogen Evolution

Abstract: Highly (001)-textured, photoactive WSe2 thin films have been prepared by an amorphous solid-liquid-crystalline solid process promoted by palladium. By increasing the thickness of the Pd promoter film (≥10 nm) the structure and texture of the WSe2 films can be improved significantly. However, these as-crystallized WSe2 films are only weakly photoactive in a 0.5 М H2SO4 electrolyte under AM 1.5 solar irradiation which we attribute to an inefficient photogenerated charge transfer across the WSe2/electrolyte inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 35 publications
5
46
0
Order By: Relevance
“…The AM 1.5-spectrum integrated photocurrent density of the ATM/WSe 2 photocathode from the IPCE curve is 3.1 mA cm -2 , which has been shown in our previous report 25 showed a good stability for about 2 h at a constant photocurrent density at about 1.5 mA cm -2 for polycrystalline WSe 2 thin films coated with a Pt/Cu catalyst in sulfuric acid. In our case, the stability of the ATM/WSe 2 (200 nm thick) photoelectrode was tested in 0.5 M H 2 SO 4 (0 pH) under AM 1.5 illumination.…”
Section: A B C Dsupporting
confidence: 82%
“…The AM 1.5-spectrum integrated photocurrent density of the ATM/WSe 2 photocathode from the IPCE curve is 3.1 mA cm -2 , which has been shown in our previous report 25 showed a good stability for about 2 h at a constant photocurrent density at about 1.5 mA cm -2 for polycrystalline WSe 2 thin films coated with a Pt/Cu catalyst in sulfuric acid. In our case, the stability of the ATM/WSe 2 (200 nm thick) photoelectrode was tested in 0.5 M H 2 SO 4 (0 pH) under AM 1.5 illumination.…”
Section: A B C Dsupporting
confidence: 82%
“…21 As the vdW basal planes are catalytically inert, nanoparticles are of interest for increasing the number of active sites at the edges of the hexagonal planes. 25 Recently, it was reported that ammonium thiomolybdate (NH 4 ) 2 Mo 3 S 13 nanoclusters showed an even better performance in the HER in comparison to MoS 2 nanoparticles. 22 This catalyst is characterized by a high number of catalytically active [S 2 ] 2sites.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve an efficient hydrogen evolution, the number of catalytically active sites must be increased. This can be done by Pt deposition, 19,25 which activates the grain boundaries or by chemical/electronic activation of the (00.1) vdW surfaces. The Mo 3 S 13 clusters in ATM exhibit a higher number of S-active sites compared to MoS 2 nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Even, when evaporating a thin Pt film as a HER catalyst homogeneously onto the WSe 2 van der Waals planes, no significant photocurrent can be observed. However, when depositing photochemically Pt nanoislands preferentially at the crystallite edges, 25 the transfer from the edge sites of WSe 2 crystallites to the semiconductor-electrolyte interface can be significantly improved. This clearly shows that Pt acts as a HER catalyst only at the edges of (00.1)oriented WSe 2 crystallites.…”
Section: File List (2)mentioning
confidence: 99%
See 1 more Smart Citation